Дифференциальные инварианты нестандартных проективных структур - Коновенко, Н.Г.; Лычагин, В.В. (Видавничий дім "Академперіодика" НАН України, 2008)
We describe projective structures on a line in terms of solutions of the Schrödinger equation. We give a detailed classification of projective geometrical quantities and find the algebras of their differential invariants.